Modelling of WEEE recycling operation planning under uncertainty. (10th April 2018) - Polat, Olcay; Capraz, Ozan; Gungor, Askiner
Abstract: Recycling is very important especially for hazardous materials considering their negative impacts on the environment. Waste electrical and electronic equipment (WEEE) is generally classified under hazardous waste. Determination of process methods and quantities of WEEE to be processed is significantly important since it enables the efficient operation and management of recycling systems. The presence of uncertainty in these systems requires to develop appropriate decision-making tools to deal with uncertain parameters in recycling-operation planning problems. In this study, we propose a linear programming (LP) model for multi-period operation planning for recycling of WEEE considering fuzzy parameters: demand, quantity of WEEE to be processed, operational capacity of resources, amount of output obtained from WEEE and processing times. The model aims to maximize the total profit by determining the best recycling strategies and types, quantity and stocks of WEEE to be recycled during the planning term. The solution method is based on ranking methods of fuzzy numbers through the comparison of their expected intervals. The proposed LP model is illustrated using a case study with experimental analysis. The findings indicated that the nature of fuzzy parameters have critical effect on the total cost and the total revenue at different levels. The results also show that the uncertainty in recycling of WEEE is a crucial factor in developing consistent plans to achieve the economic sustainability of recycling facilities.